Purchase Intention of Halal Toiletries: The Role of Mediating and Moderating Effects - Fiandari, Yulist Rima; Andharini, Sri Nastiti (Jurnal Manajemen Bisnis, 2024)
Research aims: This study analyzes consumers’ purchase intentions regarding halal toiletries by examining the independent variables of halal awareness, attitude, subjective norms and behavioral control. Design/Methodology/Approach: Data were collected from 260 consumers throughout questionnaires. The respondents had all purchased and used halal toiletries at least once. Hypothesis testing of the independent variable on the dependent variable was conducted using Partial Least Square (PLS) analysis, with the Smart PLS 3.0 software.Research findings: The findings indicate that halal awareness significantly influences the purchase intention of halal toiletries and has a strong impact on customer attitudes. The results also show that subjective norms influence the purchase intention of halal toiletries. Additionally, behavioral control contributes to shaping the purchase intentions. Theoretical Contribution/Originality: The study demonstrates that well-developed halal awareness significantly influences the intention to purchase halal toiletries and is a key factor in shaping consumer attitudes. The findings also highlight the role of subjective norms in forming purchase intentions, while behavioral control plays a crucial role in supporting these intentions. Practitioners/Policy Implications: The results of this study are expected to support the development of a sustainable halal industry, especially within the toiletry sector. Research Limitations/Implications: This study is limited by the indicators tested and offers opportunities for future research to explore additional variables. Future studies could incorporate a gender perspective to provide insights into differences in purchase intentions between men and women.